2017
DOI: 10.6118/jmm.2017.23.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Group Counseling on Self-care Behaviors in Menopausal Women with Diabetes

Abstract: ObjectivesDiabetes is a chronic disease which is common in menopause period. Performing self-care behaviors is effective method for control of diabetes. This study aimed to investigate the effect of counseling on self-care behaviors in menopause diabetes women in 2016 in Hamadan, Iran.MethodsIn this study, 80 menopausal women were randomly selected and allocated to the experimental and control groups (40 per group). Data collected by a questionnaire included of demographic information, self-care behaviors, fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The results of a study also showed the positive effect of group counseling on diabetic postmenopausal women who were recommended to have an exercise routine and a proper diet, taking dietary supplements as needed. The study showed that, after 3 months, with respect to the physical well-being, the quality of life improved in the intervention group [33]. Exercise, proper diet, and daily walks for at least 20 minutes were also included in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…The results of a study also showed the positive effect of group counseling on diabetic postmenopausal women who were recommended to have an exercise routine and a proper diet, taking dietary supplements as needed. The study showed that, after 3 months, with respect to the physical well-being, the quality of life improved in the intervention group [33]. Exercise, proper diet, and daily walks for at least 20 minutes were also included in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…This was done in six stages by one of the researchers who was a master student in midwifery counseling for the intervention group in the meeting hall of Javanrood City Health Center. 25,26 The content used in the counseling sessions was prepared by two researchers using related books and articles. Then the content was studied and approved by five faculty members of the Hamadan Nursing and Midwifery Faculty (Table 1).…”
Section: Interventionmentioning
confidence: 99%
“…The GATHER model is a counseling model that can be used both individually, and in groups 21 . Various studies have shown the positive effects of this model in the field of women's health 22-25 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Menopause is a period in the life cycle of all women and is associated with hormonal changes,12 that presents with different symptoms, including hot flashes, night sweat, vaginal atrophy, stress, apprehension and decreased libido 3. Hormone replacement therapy (HRT) is a widely used therapeutic approaches to deal with menopausal symptoms 4.…”
Section: Introductionmentioning
confidence: 99%